Binding site multiplicity with fatty acid ligands: Implications for the regulation of PKR kinase autophosphorylation with palmitate. Issue 10 (3rd June 2014) - Fang, Liang; Cho, Hyun Ju; Chan, Christina; Feig, Michael
ABSTRACT Saturated long chain‐free fatty acids (FFAs), especially palmitate, have been implicated in apoptosis by inhibiting the activity of PKR (double‐stranded RNA‐dependent protein kinase). We recently found evidence that palmitate interacts directly with the kinase domain of PKR, subsequently inhibiting the autophosphorylation of PKR. To investigate the interactions of palmitate with PKR and its effects on PKR autophosphorylation, we performed extensive unbiased MD simulations combined with biochemical and biophysical experiments. The simulations predict multiple putative binding sites of palmitate on both the phosphorylated and unphosphorylated PKR with similar binding affinities. Ligand‐protein interactions involving a large variety of different binding modes challenge the conventional view of highly specific, single binding sites. Key interactions of palmitate involve the αC‐helix of PKR, especially near residue R307. Experimental mutation of R307 was found to affect palmitate binding and reduce its inhibitory effect. Based on this study a new allosteric mechanism is proposed where palmitate binding to the αC‐helix prevents the inactive‐to‐active transition of PKR and subsequently reduces its ability to autophosphorylate. Proteins 2014; 82:2429–2442. © 2014 Wiley Periodicals, Inc.